Analisis Kualitas Pelayanan Dalam Perspektif Survei Kepuasan Masyarakat di Kelurahan Semolowaru Kota Surabaya - Elok Gita Cahyani; Sri Umiyati; Wildan Taufik Raharja (FISIP UWP, 2023)
The aim of the study was to analyze the quality of service at the Semolowaru Village Office, Surabaya City in the SKM perspective according to PermenPAN & RB No. 14 of 2017 which has 9 service elements, which uses a type of quantitative descriptive research and the type of data collection uses observation, questionnaires, and documentation, while the data analysis technique uses SKM calculations in accordance with PermenPAN & RB No. 14 of 2017. The research method uses qualitative methods. Data analysis in this study used quantitative methods to produce descriptive data to describe the actual situation, which did not use statistical calculations but by reading tables, graphs or figures. Research methods are research procedures and techniques Based on the results of the analysis, it can be seen that service quality in the SKM perspective at the Semolowaru Village Office, Surabaya City, obtained an SKM conversion result of 78.03. The performance of the Semolowaru Village Office, Surabaya City, is in the service quality